2021
DOI: 10.1101/2021.08.23.457441
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wolbachia in scale insects: a distinct pattern of infection frequencies and potential transfer routes via ant associates

Abstract: Wolbachia is one of the most successful endosymbiotic bacteria of arthropods. Known as the master of manipulation, Wolbachia can induce a wide range of phenotypes in its host that can have far-reaching ecological and evolutionary consequences and may be exploited for disease and pest control. However, our knowledge of Wolbachia's distribution and infection rate is unevenly distributed across arthropod groups such as scale insects. We fitted a distribution of within-species prevalence of Wolbachia to our data a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 117 publications
3
5
1
Order By: Relevance
“…Intimacy of direct physical interaction between ants and scale insects may provide a route of microbial exchange, as seen in other hemipteran groups (Ivens et al, 2018;Pringle & Moreau, 2017). In a previous study, a positive correlation between Wolbachia infection in scale insects and their associates indicated that ants may play a role in host-shifting (Sanaei, Lin, et al, 2021). Here, we found that only one out of five case of infected ant-scale insect pairs shares the same Wolbachiastrain.…”
Section: Role Of Scale Insect Associate Species In Wolbachia Host Shiftssupporting
confidence: 65%
See 3 more Smart Citations
“…Intimacy of direct physical interaction between ants and scale insects may provide a route of microbial exchange, as seen in other hemipteran groups (Ivens et al, 2018;Pringle & Moreau, 2017). In a previous study, a positive correlation between Wolbachia infection in scale insects and their associates indicated that ants may play a role in host-shifting (Sanaei, Lin, et al, 2021). Here, we found that only one out of five case of infected ant-scale insect pairs shares the same Wolbachiastrain.…”
Section: Role Of Scale Insect Associate Species In Wolbachia Host Shiftssupporting
confidence: 65%
“…While we do not have enough statistical power to test which route of transfer is the most common and in which directions these transfers take place, our data support the hypothesis that the associates tested in the current study play a role in host shifting. Although positive correlations were not previously observed between infection of scale insects and their associates (Sanaei, Lin, et al, 2021), here we observed sharing similar Wolbachia strains between pairs of scale insect and not only ants but also wasps, beetles and flies (File S3). In addition, infection by the super-spreader stain "w Sph1" of several species of scale insects, ants, and wasps is another source of evidence for a substantial contribution of associate species in Wolbachia host-shifting in scale insects.…”
Section: Role Of Scale Insect Associate Species In Wolbachia Host Shiftssupporting
confidence: 48%
See 2 more Smart Citations
“…In particular, many are usually observed in close interactions with ants through trophallaxis (where the honeydew produced by the scale insects is consumed by ants) (Buckley & Gullan, 1991;Gullan et al, 1993;Hölldobler et al, 1990). Despite several similarities with other hemipterans, Sanaei, Lin, et al (2021) found that most species are predicted to have low to intermediate Wolbachia prevalence, in contrast to a u-shaped distribution (most species have a very low or very high prevalence) predicted for other groups (Hilgenboecker et al, 2008). Also, a positive correlation between Wolbachia infection in scale insects and their associate ants indirectly points to a plausible route of transfer (Sanaei, Lin, et al, 2021).…”
mentioning
confidence: 99%